Implikasi Bahasa Arab Pada Hadis Dan Sunnah (Ontologi, Epistemologi Dan Aksiologi) - Ali Fathurrahman; Erwin Hafid; Abustani Ilyas; Baiq Raudatussolihah (CV. SINAR HOWUHOWU, 2026)
Arabic holds a strategic position in understanding the hadith and sunnah of the Prophet Muhammad (peace be upon him) as a source of Islamic teachings after the Qur'an. Hadith and sunnah were conveyed, narrated, and codified in Arabic, which has complex linguistic characteristics and is rich in meaning. This article aims to analyze the implications of Arabic on hadith and sunnah from the perspectives of ontology, epistemology, and axiology. This study uses a qualitative approach with a library research method through an analysis of classical and contemporary literature relevant to the study of Arabic and hadith science. The results of the study indicate that ontologically, Arabic is an existential medium that determines the structure and authentic meaning of hadith and sunnah. Epistemologically, mastery of Arabic serves as the main methodological instrument in acquiring, interpreting, and verifying hadith knowledge through linguistic sciences. Meanwhile, axiologically, a comprehensive understanding of Arabic has implications for the application of hadith and sunnah values ​​​​contextually, moderately, and oriented towards the benefit. Thus, Arabic cannot be separated from the study of hadith and sunnah, both at the conceptual and practical levels, so that strengthening Arabic language competence is an urgent need in the development of contemporary Islamic studies.